2019
DOI: 10.1371/journal.pone.0217535
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transitional health management on adherence and prognosis in elderly patients with acute myocardial infarction in percutaneous coronary intervention: A cluster randomized controlled trial

Abstract: Purpose This study aimed to assess the effects of transitional health management on adherence and prognosis in elderly patients with acute myocardial infarction undergoing percutaneous coronary intervention. Methods We conducted the trial from June 2016 to December 2016. A total of one hundred and fifty patients with acute myocardial infarction after PCI who met the inclusion criteria were randomly divided into an experimental (n = 75) group and a control (n = 75) group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 27 publications
(31 reference statements)
0
21
0
4
Order By: Relevance
“…A randomized clinical trial divided with 140 elders after acute myocardial infarctions in two groups (control and intervention), and found that the intervention group, which received telephone follow up about the treatment of the disease from health workers for 12 weeks after a hospital discharge related to the ischemic event, showed a better adherence to the drug therapy and to the healthy lifestyle, with lower rates of adverse effects and readmissions. All variables compared were statistically significant (27) .…”
Section: Discussionmentioning
confidence: 91%
“…A randomized clinical trial divided with 140 elders after acute myocardial infarctions in two groups (control and intervention), and found that the intervention group, which received telephone follow up about the treatment of the disease from health workers for 12 weeks after a hospital discharge related to the ischemic event, showed a better adherence to the drug therapy and to the healthy lifestyle, with lower rates of adverse effects and readmissions. All variables compared were statistically significant (27) .…”
Section: Discussionmentioning
confidence: 91%
“…This result can be related to the fact that the patients did not consider it lack of adherence when they forget to take their medications at the prescribed times. Other studies have also shown that a large number of patients reported neglecting the medication schedule ( 8 , 10 , 20 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also emphasize that the difficulty of physical access (due to distance or limited means of transportation) and the difficulties in accessing the medications also contribute to lack of adherence ( 8 , 17 ) . The individuals who have a health insurance tend to use the services more and, in turn, attend to medical appointments more often, thereby increasing the opportunity to access information that can support adherence ( 10 ) . One of the main benefits of easy access to the health care services is the possibility of therapeutic adjustments and monitoring ( 17 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-acute hospital-to-home healthcare programmes have been suggested to improve medication adherence and clinical indicators, and to reduce rates of adverse cardiovascular events and rehospitalisation [ 40 ]. The broader adherence measures of ASHRO predictive models developed for populations with prior hospitalisation for cardiovascular disease may reflect the healthcare provided in transitional care.…”
Section: Discussionmentioning
confidence: 99%